PENGARUH KOMUNIKASI GURU TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PAI MELALUI PERILAKU SISWA SEBAGAI VARIABEL KELAS VIII DI MTs TAJHIZ DINIYAH MESKOM BENGKALIS - Azrin, Hasnita; Chanifudin, Chanifudin (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Education is a very decisive process in achieving the best quality of human resources because it is quite realized that the progress of society can be seen from the development of educators. The teacher's communication skills determine success in helping students to better understand the material to be delivered. This study aims to determine the Influence of Teacher Communication on Learning Outcomes in Pie Subjects through Student Behavior as a Class VIII Variable at Mts Tajhiz Diniyah Meskom. This type of research is quantitative descriptive research with a study population of 48 grade VIII students at MTs Tajhiz Diniyah Meskom with the Saturated Sample technique. The research instruments used are questionnaires and documentation. The results showed that the Sig value for the effect of X1 on X2 was 0.730 > 0.05 and the calculated value was -3.84 < table 2.014, so it can be concluded that Teacher Communication has a negative influence on Learning Outcomes, as for the purpose of the explanation above, that is, when the value of the teacher communication variable (X1) increases by 1 unit, then the value of the student learning outcome variable (X2) decreases by -0.62. This means that here there is a negative correlation between 2 independent variables, namely, between teacher communication and student learning outcomes. Furthermore, based on the simultaneous hypothesis test, F states that there is a positive influence and significance between teacher communication and student behavior together on learning outcomes in PAI subjects in MTs Tajhiz Diniyah Meskom or Ha 2 accepted